Rakhuin` prann` nay` vati le rap` rhi rhe mon` ceti pathui mya = ancient pagodas from four wadys of Rakhine state - Hlaing, Myat Min.; Soe Myint, U . (Yangon : U Soe Myint, 2000)
Description of Buddhist pagodas and temples in Rakhine state, Burma.
"Compiled by Myat Min Hlaing, translated by Soe Myint" -- back cover.
In Burmese and English (some parts appear in parallel translation).
Keywords: Buddhist temples -- Burma -- Rakhine state